Global warming: An investigation of the evidence, the implications and the way (The complete briefing) - John Houghton (Lion Book, 1994)
The book describes the science of global warming, its impacts and what action might be taken in a way which the intelligent non-scientist can understand. This book is divided into 12 chapters. Chapter 1, global warming and climate change. Chapter 2, greenhouse effect. Chapter 3, greenhouse gases. Chapter 4, climates of tthe Past. Chapter 5, modelling the climate. Chapter 6, climate change under business-as-usual. Chapter 7, the impacts of climate change. Chapter 8, Why should we be concerned. Chapter 9, weighing the uncertainty. Chapter 10, action to slow and stabilize climate change. Chapter 11, energy and transport for the future. Chapter 12, the global village